Economics of Sovereign Wealth Funds. - Das, Udaibir S. (Books., 2010)
The book covers a wide range of topics of relevance to policymakers in countries that have sovereign wealth funds (SWFs) and those that receive SWF investments. Renowned experts in the field have contributed chapters. The book is organized around four themes: (1) the role and macrofinancial linkages of SWFs, (2) institutional factors, (3) investment approaches and financial markets, and (4) the postcrisis outlook. The book also discusses the challenges facing sovereign wealth funds in the coming years, from an inside perspective on countries, including Canada, Chile, China, Norway, Russia, an.